Validation study of the Amharic version Safety Attitudes Questionnaire (SAQ) in public hospitals of Addis Ababa, Ethiopia: a cross-sectional study - Bisrat Tamene Bekele; Trhas Tadesse Berhe; Biniam Yohannes Wotango; Wubet Mihretu Workneh; Nebiyou Wendwessen (BMC, 2024)
Abstract Background In Ethiopia, there is a growing concern about improving patients' safety in healthcare facilities. However, the lack of a valid and reliable instrument sensitive to the Ethiopian culture for measuring health professional practice environment leads to difficulty in constructing evaluations of safety climate and further linking organizational research to outcomes research. This research study examined the psychometric properties of the Safety Attitude Questionnaire (SAQ) in the Amharic language within an Ethiopian healthcare context. Method A hospital-based cross-sectional study design was conducted. The SAQ was meticulously translated into Amharic using forward and backward translation methods. Content validity was evaluated with input from seven patient safety and healthcare quality experts. Face validity was established through feedback from healthcare professionals. Then, the Amharic SAQ (SAQ-A) was distributed to 648 participants working in 11 public hospitals, and a total of 611 valid questionnaires were completed and returned (95.2% response rate). Cronbach's alpha, McDonald's omega, composite reliability, correlation analysis, and average variance estimation were calculated, and confirmatory factor analysis was performed. Descriptive analyses were performed to describe socio-demographic characteristics. A P-value of ≤0.05 was considered statistically significant. Tables, figures, charts, and texts are used for data presentation. Result The overall internal consistency (Cronbach's alpha) for the 31-item SAQ-A was 0.903, indicating excellent reliability. Confirmatory factor analyses demonstrated a good model fit for each dimension and the entire construct (χ2=1086.675, df=412, p<0.001, comparative fit index (CFI)=0.923, Tucker Lewis index (TLI)=0.913, and root mean square error of approximation (RMSEA)=0.052). The positive response rate of healthcare workers in hospitals was 32.1%. The positive response rates of the six dimensions were teamwork climate (59.7%), safety climate (41.9%), job satisfaction (57.1%), working conditions (37.5%), perception of management (37.6%), and stress recognition (46.2%). Conclusion The Amharic translation of the SAQ showed good psychometric properties, making it a valuable tool for assessing safety attitudes among Amharic-speaking Ethiopian healthcare practitioners.